AN ANALYSIS OF THE TRANSLATION PROCEDURES ON THE SCALES OF FORMALITY USED BYTHE BLACK AMERICANS IN A DRAMA MOVIE ENTITLED"THE PURSUIT OF HAPPYNESS" - Yana Muhammad Fauji, - (2011)
The research is entitled "An Analysis of the Translation Procedures on the Scales of Formality Used by the Black Americans in a Drama Movie Entitled The Pursuit of Happyness". The study was aimed to find out the scales of formality used by the Black Americans in their interaction, to identify the degrees of equality of the formality scales in the source language (SL) to be translated in the target language (TL), and to find out the translation procedures used to translate the scales of formality. The study employed descriptive qualitative method. The data were taken from the movie script. There were 210 items of sample drawn randomly from the Black Americans' dialogues in the movie script. The scales of formality were analyzed by using the theory of the scales of formality proposed by Joos (1967). And then, the degrees of equality of the formality scales were analyzed by using the explanation of the degree of equality according to Munday and Basil (2004) and Catford (1965). Finally, the translation procedures in translating the scales of formality were analyzed by using the theory of the translation procedures proposed by Newmark (1988). The findings of the study showed that there were 11 translation procedures with the total 325 translation procedures usages used to translate 210 items of sample of the scales of formality. From 77 translation procedures usages used to translate 40 items of the Formal scales which were equal in SL and in TL, synonymy and through-translation were the most dominant translation procedures with 26 usages (34 %) and 19 usages (25 %). And from 87 translation procedures usages used to translate 53 items of the Casual scales which were equal in SL and in TL, synonymy and through-translation were also the most dominant translation procedures with 28 usages (32 %) and 20 usages (23 %). And then, through-translation was the most dominant translation procedure used to translate 39 items of the Consultative scales and 22 items of the Intimate scales which were equal in SL and in TL with 28 usages (46 %) from 61 translation procedures usages and 8 usages (36 %) from 22 translation procedures usages. Finally, from 25 translation procedures usages used to translate 19 items of increasing scales, expansion was the most dominant translation procedure with 8 usages (32 %), and from 53 translation procedures usages used to translate 37 items of decreasing scales, reduction was the most dominant translation procedure with 28 usages (53 %).